Association of the triglyceride glucose index with obesity indicators and hypertension in American adults based on NHANES 2013 to 2018 - Pingping Huang; Hongwei Zhang; Gaocan Ren; Yifei Wang; Shuangqing Fu; Yicheng Liu; Zhibo Zhang; Lijun Guo; Xiaochang Ma (Scientific Reports)
Abstract This cross-sectional study aimed to investigate the association between the TyG index and both obesity indicators and hypertension among American adults. Data were drawn from 4,813 adults in the 2013–2018 National Health and Nutrition Examination Survey (NHANES). Multivariate logistic regression models indicated significant associations between TyG and obesity-related indices with hypertension. Using Cox regression analysis, we examined the relationship between TyG and obesity-related indices in relation to hypertensive prognosis, employing threshold effect analysis and fitted smoothed curves for consistency. Subgroup analyses and interaction tests were conducted. Results showed strong correlations between TyG, TyG-BMI, TyG-WHtR, TyG-WC and hypertension, with odds ratios (ORs) of hypertension rising across TyG quartiles (Q1–Q4). Cardiovascular mortality analysis revealed that TyG (HR = 1.89, 95% CI (1.03,3.51), P < 0.05) and the Q2 group (HR = 4.93, 95% CI (1.29,18.80), P < 0.05) were significantly associated with increased risk. A positive correlation between TyG and hypertension was noted below a threshold of 8.1, with inverse associations beyond this point. The TyG-BMI, TyG-WHtR, and TyG-WC exhibited positive correlations with hypertension, although weakened after reaching a certain threshold. These findings suggested that TyG and related indices are associated with hypertension and may aid in understanding risk stratification in this context.